Implementasi Ekstrakurikuler Pramuka Dalam Penanaman Nilai Pendidikan Karakter Pada Pelajar Di SD Negeri 104202 Bandar Setia - Fadilla Tussyah Raini; Irda Yani Dongoran; Khadijah Gani Harahap; Fajar Siddik Siregar (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This research aims to analyze the implementation of Scout extracurricular activities in instilling character education values in students at SDN 104202 Bandar Setia. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. The research results show that Scout activities at this school play a significant role in instilling character values such as discipline, responsibility, cooperation and honesty. Scouting activities, including regular drills, camps, and social activities, provide opportunities for students to practice and strengthen these values. Scout leaders also play an important role in directing and providing real examples of the application of character values in everyday life. Thus, Scout extracurricular activities at SDN 104202 Bandar Setia are effective in supporting the character education program launched by the school.